Defining the Yangtze–Cathaysia suture zone in South China using ambient noise tomography. Issue 1 (2nd March 2023) - Ma, Junwei; Guo, Zhen; Huang, Jingqiu; Fu, Yuanyuan V; Barnard, Alex
SUMMARY: The South China Craton formed after collision between the Yangtze and Cathaysia Blocks. The suture zone between these two blocks is the crux of understanding the geological evolution of South China. Due to the relative paucity of high-resolution subsurface data, the location of the suture zone in the southwestern region remains uncertain. To find the suture zone, we created a high-resolution model of the crust and upper mantle structure using 27 months of continuous waveform data acquired from 457 stations in South China. The model uses extracted phase velocity dispersion curves of Rayleigh waves at 4–40 s from ambient noise cross-correlation functions, to perform a direct inversion for an azimuthal anisotropic V SV model. In the crust a prominent belt of strong azimuthal anisotropy exists between the Yangtze and Cathaysia Blocks. The fast polarization axes in this belt correspond to the NE-trending orogen between the two blocks. In the deeper crust of the Cathaysia Block we image multiple areas of diffuse low-velocity anomalies. As defined by the margins of the strongly anisotropic belt, the Yangtze–Cathaysia suture zone is delineated by lines that traverse: Shaoxing–Jiangshan–Pingxiang–Longsheng–Hechi and Shitai–Jiujiang–Yueyang–Dayong–Jishou. Further analysis of the seismic data links deep low velocities with widespread Late Mesozoic magmatism in the Cathaysia Block. The deep low velocities are likely a result of dehydration of the subducting Pacific Plate causing mantle upwelling and underplating.